1994
DOI: 10.1073/pnas.91.18.8587
|View full text |Cite
|
Sign up to set email alerts
|

Extent of terminal complementarity modulates the balance between transcription and replication of vesicular stomatitis virus RNA.

Abstract: We compared the templae properties of a subgenomic RNA that onaed the authentic 5' and 3' ends of the vesicular stomat virus genome with those of RNAs in which the wild-tpe termini were engineered to extend their complementarity from 8 to 51 nucleotldes as seen in defective interfering RNAs. The RNA with authentic 5' and 3' ends dirted abundant t rpton but low replication. In contrast, RNAs with complement termini derived from either end of the genome replicated wellibut tra ibed poorly or not at all.These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
128
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 21 publications
6
128
0
Order By: Relevance
“…3 B, UC) especially in lanes 4-7, which probably represents a fraction of T7 primary transcript derived from vTF7-3-driven transcription of BLT δ7 that remained uncleaved at its HDV ribozyme site. Similar observations were also made by Wertz et al (1994) who worked with a vesicular stomatitis virus genome analogue and reported suboptimal cleavage at the HDV ribozyme sequence. Since the TRIzol protocol separates RNA from DNA, our total RNAs were not treated with DNase prior to Northern blot hybridization.…”
Section: Resultssupporting
confidence: 62%
“…3 B, UC) especially in lanes 4-7, which probably represents a fraction of T7 primary transcript derived from vTF7-3-driven transcription of BLT δ7 that remained uncleaved at its HDV ribozyme site. Similar observations were also made by Wertz et al (1994) who worked with a vesicular stomatitis virus genome analogue and reported suboptimal cleavage at the HDV ribozyme sequence. Since the TRIzol protocol separates RNA from DNA, our total RNAs were not treated with DNase prior to Northern blot hybridization.…”
Section: Resultssupporting
confidence: 62%
“…Terminal complementarity has also been shown to affect transcription and replication by vesicular stomatitis virus (49,50). In contrast to these examples, formation of a panhandle does not appear to play any role in the replication of respiratory syncytial virus (13) or Sendai virus (44).…”
Section: Vol 79 2005mentioning
confidence: 99%
“…In the case of other prototypic mononegaviruses such as Rous sarcoma virus, vesicular stomatitis virus, and rabies virus, this terminal complementarity includes the very first nucleotides at the 5Ј and 3Ј ends of their genomes and antigenomes (25,46,49). However, for BDV the best-fit alignment of the published sequences showed that the first three or four nucleotides remained unpaired (32).…”
mentioning
confidence: 99%
“…For members of Orthomyxoviridae (14,15) and Bunyaviridae (16,17), the formation of panhandle structures is required for efficient initiation of viral genome replication. In the case of the Mononegavirales, it is unclear whether the panhandle structure is indeed formed during viral replication (18) or whether the terminal complementarity of the genome simply reflects conserved structures of the genomic and antigenomic promoters (19).…”
mentioning
confidence: 99%